A history of Jewish-Muslim relations from the origins to the present day - Meddeb, Abdelwahab 1946-2014; Stora, Benjamin 1950-; Todd, Jane Marie 1957-; Smith, Michael B. 1940- (Princeton University Press, 2013)
Includes bibliographical references and indexes. - Published in France under the title Histoire des relations entre juifs et musulmans des origines à nos jours, c2013 Éditions Albin Michel